A new approach for improving cleaning system of air filtration in kitchen hood using liquid mist spray nozzles with non-volatile organic compound - Asmuin, Norzelawati; Osman, Kahar; Mohd Ali, Mas Fawzi; Mat Isa, Norasikin; Sies, Mohd Farid (Penerbit UTHM, 2020)
Ventilation plays an important role in providing comfortable and productive working conditions and in securing contaminant removal in a high-performance kitchen. It involves energy efficiency, indoor environment quality (IEQ), safety and air purification. The exposure to particles such as dusts, mists, gases, vapour, fumes, and etc. can cause health effects to humans. An effective way to contain this problem is the installation of Kitchen Exhaust Ventilation (KEV). KEV captures airborne particles close to the source of emission. It is generally achieved by means of an exhaust hood, ducting, air cleaner, fan and discharge which remove particles before they have a chance to escape in the kitchen. The filter used in the KEV requires periodical maintenance to ensure optimum air flow to trap the airborne particles. Normally this procedure requires removal of the filter and cleaning using chemical solvents. This project aims to implement fine spray technology in kitchen exhaust ventilation cleaning, and to introduce a non-Volatile Organic Compound (VOC) as spray cleaning solvent...